Strengthen Urban Policy and Institutions and Streamline Sector Investment for Improved Service Delivery in Pakistan : Water and Sanitation Program - World Bank Group (World Bank, Washington, DC, 2015)
This synthesis report details the process, outputs and intermediate outcomes of the above technical assistance (TA) which was aimed at service delivery improvement in urban water and sanitation, especially to the urban poor, by: (i) supporting the government in establishing efficient, autonomous and responsive utility in Peshawar; (ii) facilitating the provincial/regional governments in formulation of water sector policies; (iii) designing demand based ‘Pakistan water sector technical advisory program’ for clients; and (iv) strengthening and aligning the urban (water) reform agenda in three provincial urban units through national urban forum.